(untitled) - Noel de Nevers (New York, 1995)
The book gives an overview of air pollution control engineering: the treatment (theory and pratice), some the background for the selection of such devices (air pollution effects, the structure of U.S. air pollution law, atmospheric models, etc.)
Keywords: air - pollution,air - purification - equipment and supplies